Introduction of information communication technologies into the educational process - Nilufar Xalikova Mirkadirovna (Genius Publishing Group, 2023)
This article explores the integration of Information Communication Technologies (ICT) into the educational process. It examines the impact of technology on teaching and learning, discusses different methods for incorporating ICT in the classroom, presents the results of studies investigating the effectiveness of technology integration, and provides a discussion on the benefits and challenges associated with ICT in education. The article concludes with suggestions for maximizing the potential of ICT and fostering a successful digital learning environment.
Keywords: Information Communication Technologies; Educational Process; Technology Integration